Reduced Physical Activity Patterns in Patients with Thalassemia Compared to Healthy Controls - B. Fung, Ellen; Pinal, Jennifer; Leason, Michelle (Journal of Hematology and Oncology Research, 2015)
Background: Patients with Thal (Thalassemia) are presumed to be inactive for many of the same reasons as healthy adults, though there are limited published data to support this claim. The primary aim of this study was to compare physical activity patterns in subjects with Thal to healthy controls as well as to explore the effects of transfusion therapy on physical activity in transfusion dependent patients with Thal. Methods: 37 Thal (23 Thal major, 14 Thal intermedia, 21 Female, 27.3±10.1 years) and 30 healthy controls (17 Female, 28.0 ± 13.7 years) wore an ActiGraph accelerometer for one to two weeks. Results: Thal subjects recorded a significantly fewer total number of steps per day and lower total energy expenditure compared to healthy controls (p=0.001). None of the adult Thal subjects met the recommended 10,000 steps/day as opposed to 27% of healthy adult controls (p=0.004). Thal spent significantly less time in moderate (p=0.03) to vigorous (p=0.005) activities and more time in sedentary activity (p=0.006). Conclusion: It is now clear that Thal spend significantly less time in physically demanding activities than age-matched healthy controls, a result that has long been assumed though not previously documented. Further research is needed to define an appropriate physical activity regimen best suited for patients with Thal while examining its effect on mental and physical health.
Keywords: Thalassemia; physical activity; sleep; accelerometry; actigraph